BPMN Modeling and Information System Development at PT Maha Tour Medan Using a Design Thinking Approach - Adinda Chirilda; Suendri (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
In the digital era, property sales face significant challenges such as lengthy processes, involvement of multiple intermediaries, and lack of ownership transparency. This study aims to create a prototype property transaction system that utilizes blockchain technology, integrated with smart contracts, a Node.js backend, and a MySQL database. The system is simulated with Ganache as a local network to test the decentralized and secure data storage of transactions. The research methods include simulation and direct observation, as well as functional testing and performance evaluation using a black box testing approach to ensure the reliability and efficiency of each system component. Test results show a functional success rate of 100% from 14 test scenarios. Based on these findings, the system has been proven to validly record transactions, avoid double transactions, and maintain data integrity. Smart contract technology can partly replace notary functions digitally, while blockchain serves as a means of secure and immutable transaction storage. Therefore, this system can enhance efficiency, transparency, and accountability in property transaction processes and make a significant contribution to the digitalization of the real estate sector.